ANALYSIS OF THE QUALITY OF PHYSICS TEXTBOOKS IN THE 2013 CURRICULUM AND THE INDEPENDENT CURRICULUM - Jaya Putra, Don; Algiranto, Algiranto; Ekasari, Aprilita; Inyang, Francis (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
Similar things have also been done to support the implementation of the previous curriculum, namely the School Unit Level Curriculum and the 2023 Curriculum. This study aims to compare the quality of physics textbooks recognized by the Government in the 2013 Curriculum and the Independent Curriculum. The textbooks used as samples in this study are the 11th grade physics textbooks based on the 2013 Curriculum written by Sunardi, Paramitha Retno P., and Andreas B. Dermawan in 2016 published by Yrama Widya and the physics textbooks based on the Independent Curriculum written by Marianna Magdalena Radjawane, Alvius Tinambunan and, Suntar Jono in 2022 published by the Ministry of Education, Culture, Research, and Technology. This study uses a qualitative research approach, through literature studies. Data collection was carried out by tracing various library sources related to physics teaching materials for class XI semester I. Data processing was carried out using a comparative descriptive method which includes the method of presenting material, depth of material, novelty of content and evaluation instruments. From the results of the analysis, it was found that the physics textbook for class XI of the 2013 curriculum had better quality compared to the physics textbook for class XI of the Merdeka Curriculum both in terms of indicators of material presentation, depth of material, novelty of content and evaluation instruments.